Total Body PET Imaging From Mice to Humans - Jones, Terry (Frontiers in Physics, 2020)
Small animal PET scanning is destined to offer programs of the pre-clinical development of paradigms and protocols that are translatable for undertaking “systems biology” research in humans using total body PET Scanning.